ERRα protects against sepsis-induced acute lung injury in rats - Wenfang Xia; Zhou Pan; Huanming Zhang; Qingshan Zhou; Yu Liu (BMC, 2023)
Abstract Background Sepsis-induced acute lung injury (ALI) is associated with poor survival rates. The identification of potential therapeutic targets for preventing sepsis-induced ALI has clinical importance. This study aims to investigate the role of estrogen-related receptor alpha (ERRα) in sepsis-induced ALI. Methods Lipopolysaccharide (LPS) was used to simulate sepsis-induced ALI model in rat pulmonary microvascular endothelial cells (PMVECs). The effects of ERRα overexpression and knockdown on LPS-induced endothelial permeability, apoptosis and autophagy were determined by horseradish peroxidase permeability assay, TdT-mediated dUTP Nick End Labeling (TUNEL) assay, flow cytometry, immunofluorescence staining, RT-PCR and Western Blotting. The rat model with sepsis-induced ALI was established by cecal ligation and puncture in anesthetized rats to verify the results of in vitro experiments. Animals were randomly assigned to receive intraperitoneal injection of vehicle or ERRα agonist. Lung vascular permeability, pathological injury, apoptosis and autophagy were examined. Results Overexpression of ERRα ameliorated LPS-induced endothelial hyperpermeability, degradation of adherens junctional molecules, upregulation of bax, cleaved caspase 3 and cleaved caspase 9 levels, downregulation of anti-apoptotic protein Bcl-2 level, and promoted the formation of autophagic flux, while the knockdown of ERRα exacerbated LPS-induced apoptosis and inhibited the activation of autophagy. Administration of ERRα agonist alleviated the pathological damage of lung tissue, increased the levels of tight junction proteins and adherens junction proteins, and decreased the expression of apoptosis-related proteins. Promoting the expression of ERRα significantly enhanced the process of autophagy and reduced CLP-induced ALI. Mechanistically, ERRα is essential to regulate the balance between autophagy and apoptosis to maintain the adherens junctional integrity. Conclusion ERRα protects against sepsis-induced ALI through ERRα-mediated apoptosis and autophagy. Activation of ERRα provides a new therapeutic opportunity to prevent sepsis-induced ALI.